Implementing Geo Positioning System for Children Tracking Location Monitoring based on Android - Sari, Marti Widya; Santoso, Banu; Azman, Mohamed Nor Azhari (Scientific Journal of Informatics, 2021)
Purpose: The objectives of this research are to generate a system or application to track the whereabouts of children through smartphones that can be used by both parents of the child, and to design device that can be used practically, and children can be traced to the presence of wireless media by their parents. Improved supervision of children is needed without reducing the freedom of children to learn and explore their environment. Methods: One alternative that allows tracking the presence, location and accuracy is quite good is to use a Geo Positioning System (GPS). Result:  This GPS is packaged in a flexible form so that it can help make it easier for parents to supervise their children in the range of areas that are still accessible to them and find the child's position when separated from their parents. Novelty: The system can send the location information of children who are lost or lost on smartphone applications used by parents.